If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + 4X + 13y + 6w + 8x + -8y = 0 Reorder the terms: 4X + 4w + 6w + 8x + 13y + -8y = 0 Combine like terms: 4w + 6w = 10w 4X + 10w + 8x + 13y + -8y = 0 Combine like terms: 13y + -8y = 5y 4X + 10w + 8x + 5y = 0 Solving 4X + 10w + 8x + 5y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10w' to each side of the equation. 4X + 10w + 8x + -10w + 5y = 0 + -10w Reorder the terms: 4X + 10w + -10w + 8x + 5y = 0 + -10w Combine like terms: 10w + -10w = 0 4X + 0 + 8x + 5y = 0 + -10w 4X + 8x + 5y = 0 + -10w Remove the zero: 4X + 8x + 5y = -10w Add '-8x' to each side of the equation. 4X + 8x + -8x + 5y = -10w + -8x Combine like terms: 8x + -8x = 0 4X + 0 + 5y = -10w + -8x 4X + 5y = -10w + -8x Add '-5y' to each side of the equation. 4X + 5y + -5y = -10w + -8x + -5y Combine like terms: 5y + -5y = 0 4X + 0 = -10w + -8x + -5y 4X = -10w + -8x + -5y Divide each side by '4'. X = -2.5w + -2x + -1.25y Simplifying X = -2.5w + -2x + -1.25y
| 9.9=3x+4.2 | | 25=-3+7r | | 3(y-4)+5=4(y+2)-2y-6 | | 5m-8=-23 | | s^3-2s^2=1 | | -0.26+1.2x=2.28x+1.9 | | -12-5z=37 | | 467.14=180+0.98x | | (4x^3)-(15x^2)=0 | | 17c-2=2c | | 15x=42 | | 10n-5=2n | | -6x+5x^2+x^3=0 | | (3x-3)(3x+2)= | | (4x^3)(-15x^2)=0 | | 3y-13=y+40 | | 0.2x+0.4=-0.8 | | 6x+15-4=-2x-(-10)-7 | | -41=6x-5 | | 5=x^2-5x+2 | | 13d+7=-32 | | 7(x-2.7)=7.7 | | 3w^2-12w=12 | | 8x+3=3x+48 | | (2x-1)(x+1)=5x+5 | | -13=7h+1 | | 4x^2+3x+2=15 | | C=39.64+0.50x | | -2=5-2n | | 10(4x+1)= | | (y+2)(y+7)=0 | | 9x+8.54=6x+14 |